A Novel Phenotype of the Factor 5 Gene Mutation (Homozygote Met1736Val and Heterozygote Asp68His) Is Associated With Moderate Factor V Deficiency - Chang, Yueh-Shih; Lan, Yi-Cheng; Chen, Ya-Jyun; Huang, Jen-Seng; Yang, Chia-Ning; Huang, Chi-Ying F.; Yeh, Kun-Yun (Frontiers in Medicine, 2022)
Background Factor V (FV) deficiency is a rare disease, with a low incidence rate in Asia. Therefore, the F5 mutation in the Taiwanese population is poorly understood. Methods A Chinese family with FV deficiency was included, and the patient and his family members underwent mutation analysis. Then, patients from Keelung City (Taiwan) were screened for F5 polymorphism; the Chang Gung Human Database was used to determine single-nucleotide variants in the non-FV-deficient patient population. Results Eight mutation sites on the F5 gene locus, including exon 16 homozygote Met1736Val and seven heterozygous mutations, including Asp68His, were found. Moreover, Met1736Val was found to be the dominant mutation in people living in the Taiwan community, and this result was compared with the records of the Chang Gung Human Database. The above-mentioned polymorphisms may result in a variable incidence of FV deficiency in Keelung City, thereby facilitating carrier diagnosis and prenatal diagnosis in most FV-deficient families. Conclusion The homozygote Met1736Val and the co-inheritance of the Asp68His F5 gene are unique and worthy of screening in FV-deficient patients.